2021
DOI: 10.1186/s13287-021-02481-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from mesenchymal stromal cells mediate endogenous cell growth and migration via the CXCL5 and CXCL6/CXCR2 axes and repair menisci

Abstract: Background Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) are promising candidates for tissue regeneration therapy. However, the therapeutic efficacy of MSC-EVs for meniscus regeneration is uncertain, and the mechanisms underlying MSC-EV-mediated tissue regeneration have not been fully elucidated. The aims of this study were to evaluate the therapeutic efficacy of intra-articular MSC-EV injection in a meniscus defect model and elucidate the mechanism underlying MSC-EV-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…The ability of EV to stimulate cell migration has already been reported by several groups for different cell sources. The cancer cell-derived EV were shown to modulate the dissemination pattern of metastatic cells [ 43 ] and, in particular, MSC-EV have been seen to stimulate chondrocyte and synovial MSC migration via the CXCL5 and CXCL6/CXCR2 axes [ 12 ]. However, none of these studies referred to glycan-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of EV to stimulate cell migration has already been reported by several groups for different cell sources. The cancer cell-derived EV were shown to modulate the dissemination pattern of metastatic cells [ 43 ] and, in particular, MSC-EV have been seen to stimulate chondrocyte and synovial MSC migration via the CXCL5 and CXCL6/CXCR2 axes [ 12 ]. However, none of these studies referred to glycan-dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is widely accepted that EV cargo (lipids, RNA and proteins) can be shuttled to the target cells by endocytosis (clathrin-dependent or caveolae-dependent) [ 3 , 4 , 5 , 6 ], phagocytosis [ 7 ], macropinocytosis [ 8 ] or by plasma/endosomal membrane fusion in acidic pH conditions, when EV and cells’ plasma membrane display the same fluidity [ 9 ]. Moreover, it has also been established that this transfer of vesicular content plays a crucial role in the intercellular communication in several biological processes, including angiogenesis [ 10 , 11 ], cell migration [ 12 ], inflammation regulation [ 13 , 14 ], bone formation [ 15 ] or interneuronal communication [ 16 ]. The transcriptomic, proteomic and lipidomic profiles of EV have been widely studied to find the molecules implicated in EV–cell interaction [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, MSCs can also differentiate into ligament fibroblasts, contributing to the regeneration of cruciate ligament, and the differentiation process can be regulated ( 44 ). In addition, it can also promote the repair of meniscus injury ( 45 ). Platelet-rich plasma (PRP) is a product of platelet concentration obtained from peripheral blood after repeated centrifugation, which has been used in clinical treatment since the 1980s ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…36 Extracellular vesicles (e.g., exosomes) secreted from MSCs have been reported to be able to enhance cartilage regeneration, maintain chondrocyte homeostasis and delay OA progression in preclinical in vitro and in vivo studies. [37][38][39] The chondrogenic properties of exosomes derived from IFP-MSCs were recently described in a preclinical study, which found that IFP-MSCs secrete a large amount of miR-100-5pabundant exosomes that protected chondrocytes from cell apoptosis and ameliorated OA progression in mice. 40 Cocultures of chondrocytes and IFP-MSCs can promote chondrogenic differentiation of IFP-MSCs, 41 and suppression of chondrocyte inflammation and MSC hypertrophy when compared to either of the cell populations cultured alone.…”
Section: Ifp-derived Mscs (Ifp-mscs) and Cartilagementioning
confidence: 99%
“…Moreover, human IFP‐MSCs show a higher chondrogenic differentiation potential than MSCs isolated from body fat tissue and bone marrow 36 . Extracellular vesicles (e.g., exosomes) secreted from MSCs have been reported to be able to enhance cartilage regeneration, maintain chondrocyte homeostasis and delay OA progression in preclinical in vitro and in vivo studies 37–39 . The chondrogenic properties of exosomes derived from IFP‐MSCs were recently described in a preclinical study, which found that IFP‐MSCs secrete a large amount of miR‐100‐5p‐abundant exosomes that protected chondrocytes from cell apoptosis and ameliorated OA progression in mice 40 …”
Section: Interactions Between the Ifp And Cartilagementioning
confidence: 99%